Music and technology in the twentieth century - Braun, Hans-Joachim (Baltimore John Hopkins University Press, 2002)
Technology has always been inseparable from the development of music. But in the twentieth century a rapid acceleration took place: a new "machine music" came into existence, electronic musical instruments appeared, and composers sometimes seemed more like sound technicians than musicians. In this book Hans-Joachim Braun and his co-authors offer a wide-ranging and fascinating look at the relationship of technology and modern music. Topics range from the role of Yamaha in Japan's musical development to the social construction of the synthesizer; from the player piano as precursor of computer music to the musical role of airplanes and locomotives; from the growth of one independent recording studio (from "Polka to Punk") to the origins of the 45-RPM record. Other chapters consider violin vibrato and the phonograph, Jimi Hendrix, and the aesthetic challenge of soundsampling. The book concludes with a look at the current situation, and perspectives for its future in electronic music. Contributors: Barbara Barthelmes, Karin Bijsterveld, Hans-Joachim Braun, Martha Brech, Hugh Davies, Bernd Enders, Geoffrey Hindley, Juergen Hocker, Mark Katz, Tatsuya Kobayashi, James P. Kraft, Alexander B. Magoun, Rebecca McSwain, Andre Millard, Helga de la Motte-Haber, Trevor Pinch, Susan Schmidt-Horning, and Frank Trocco.